Profit Management, Capital Intensity, Gender Diversity, On Tax Avoidance with Corporate Sustainability as An Intervening Variable - Reskino Reskino; Prankyanto Tambunan (Jurnal Indonesia Sosial Sains, 2023)
The highest income in Indonesia comes from tax revenue. High and low tax revenues will determine the state budget in financing public expenditures. So awareness is needed for taxpayers or entities to pay their tax obligations. The purpose of the study is to empirically prove or analyze the effect of profit management on tax avoidance. This research uses quantitative methods, namely research procedures that produce data in the form of numbers and are generally analyzed using descriptive statistics with the source of data taken in this study is secondary data. The results of hypothesis testing in table 4 show that the t-Statistic value is 4.393073, while the prob. From profit management is 0.0000 which means 0.0000 < 0.05 indicates that profit management variables affect tax avoidance. The conclusions obtained are based on phenomena, problem formulations, hypotheses and research results conducted on manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period, it can be concluded that simultaneously the variable of profit management has a positive effect on tax avoidance.